Left Hemibody Swelling in an HIV-Positive Patient with Congenital Heart Disease - Matteo Boattini; André Almeida; Rita Barata Moura; Miguel Toscano Rico (Case Reports in Vascular Medicine)
We report the case of a 50-year-old HIV-positive woman with a congenital cyanotic heart disease who developed left axillary, subclavian, and brachiocephalic vein thrombosis and left lower aortopulmonary collateral arterial thrombosis, presenting as left hemibody swelling. We also briefly overview the literature regarding upper extremity deep vein thrombosis (UEDVT). Given the absence of other risk factors, it was our firm believe that our patient's UEDVT was due to a hypercoagulable state associated with congestive heart failure (CHF) and HIV infection.